Educational needs and its associated factors among patients with ankylosing spondylitis in China: a multicenter cross-sectional study - Song, Yuqing; Shen, Weiping; Deng, Xue; Xing, Lu; Tang, Yuping; Liu, Mei; Jiang, Qiaolin; Chen, Yanling; He, Benyi; Wang, Li; Tang, Fangmei; Wu, Jianmei (Frontiers in Public Health, 2024)
Objective: Patient education is an important part of ankylosing spondylitis (AS) management. Effective patient education should be targeted at specific priorities and needs of the patients. However, the educational needs of patients with AS in China have not been systematically explored. The purpose of this study is to assess the level of educational needs and analyze associated factors in patients with AS in China. Methods: This multicenter cross-sectional study was conducted at five hospitals in China. The Chinese version of the Educational Needs Assessment Tool (ENAT) was used to measure educational needs. Disease activity and physical function were assessed using the Bath Ankylosing Spondylitis Functional Index (BASFI), and Bath Ankylosing Spondylitis Disease Activity Index (BASDAI). Multiple linear regression analysis was used to identify the predictors of educational needs. Results: This study included 163 patients with AS. The mean ENAT score was 86.25(31.64). Patients wanted to know more about arthritis process, self-help measures, and treatments. Multivariate linear regression analysis indicated that younger age, female, higher disease activity, and no family history of AS (P<0.05) were positive predictors of educational needs. Conclusion: Patients with AS in China have considerable educational needs, particularly in the domains of arthritis, self-help, and treatment. Female patients and patients with younger age, higher disease activity, and no family history may have higher educational needs. These factors should be considered when conducting need-based patient education programs. Healthcare professionals should integrate need-based patient education into rheumatology care in the future.